Identification of differential gene expression related to reproduction in the sporophytes of Saccharina japonica - Uji, Toshiki; Kandori, Takuya; Mizuta, Hiroyuki (Frontiers in Plant Science, 2024)
Saccharina japonica, a significant brown macroalga in the Pacific Ocean, serves as a food source and industrial material. In aquaculture, collecting mature sporophytes for seedling production is essential but challenging due to environmental changes. In this study, transcriptomic analysis of vegetative and sorus tissues was done to identify differentially expressed genes (DEGs) and enhance our understanding of sorus formation regulation in S. japonica. KEGG pathway and Gene Otology (GO) analysis revealed that upregulated DEGs were involved in folate biosynthesis, riboflavin metabolism, and amino acid biosynthesis. In addition, the upregulation of genes associated with cell wall remodeling, such as mannuronan C-5-epimerases, vanadium-dependent haloperoxidases, and NADPH oxidase, was observed in sorus parts. Meanwhile, downregulated DEGs in sorus portions included genes related to chloroplast function. These findings will help us understand the regulatory mechanisms behind sorus formation in S. japonica and extracellular matrix remodeling in brown algae.